A single blind randomized study on the effectiveness of the Kenneth Reed mandibular nerve block versus the conventional inferior alveolar nerve block in walk-in patients at UP Manila College of Dentistry - Rodriguez, Ramon Carlos P.; Tingson, Keneshia Chantelle N.; Escoto, Elmer Jesus
Introduction: The conventional IANB is commonly used for mandibular molar extraction. Reported disadvantages were pain upon injection, delay in time of onset and failure to provide sustained effect during extraction. By making the injection site 1 cm higher in Kenneth Reed nerve block, it could compensate for the anatomic variations such as the location of lingula, the target where the mandibular nerve passes before it enters the mandibular canal. The advantage is landmark stability and less vascular injection site. It is being used on Caucasians and has produced the desired effects. To prove true in Filipinos, effectiveness of the blocks was compared on UPCD patients using parameters such as pain upon administration, aspiration rate, time of onset and profoundness.
Methodology: Anesthesia was administered using the two nerve blocks on 14 patients who were divided evenly in two groups through random allocation. Anxiety level was evaluated before the techniques were performed by the faculty co-author who is a licensed oral surgeon. The parameters were then recorded and the dental extracts proceeded. Effectiveness was assessed using the 5 parameters interpreted through observations of the exhibited results of each block. The rate of pain upon administration, aspiration rate, onset time of subjective and objective symptoms and the percentages of grade A, B and C for the profoundness were recorded.
Results: There were no positive aspirations for both groups. One patient felt pain upon needle insertion on the 1st group and three patients on the 2nd group. The mean time of onset for the subjective sympton for the first group was 2 minutes 42 seconds while on the second group was 8 minutes 13 seconds with three blocks failing to produce anesthesia in the first 10 minutes after the administration. The mean onset time for the objective symptoms in group 1 is 2 minutes 48 seconds while in group 2 is 8 minutes 40 seconds. Profoundness on the first group was 56% grade A. 29% grade B and 14% grade C. On the second group, 57% grade A while 14% grade B and 29% grade C.
Conclusion. The conventional IANB is still the better block to use in Filipino patients.
Thesis--(Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Anesthesia; Inferior Alveolar Nerve Block (IANB).; Kenneth Reed Block (KRB).